2018
DOI: 10.1089/soro.2017.0008
|View full text |Cite
|
Sign up to set email alerts
|

A Reconfigurable Omnidirectional Soft Robot Based on Caterpillar Locomotion

Abstract: A pneumatically powered, reconfigurable omnidirectional soft robot based on caterpillar locomotion is described. The robot is composed of nine modules arranged as a three by three matrix and the length of this matrix is 154 mm. The robot propagates a traveling wave inspired by caterpillar locomotion, and it has all three degrees of freedom on a plane (X, Y, and rotation). The speed of the robot is about 18.5 m/h (two body lengths per minute) and it can rotate at a speed of 1.63°/s. The modules have neodymium-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 33 publications
0
78
0
3
Order By: Relevance
“…Copyright 2017, Mary Ann Liebert Inc. D) An omnidirectional soft robot consisting of nine (left) and three (right) modules, E) deformation of the soft cylinder under various conditions, and F) mechanism of crawling gait including contracted (red), pressurized (blue), and structure parts (green). Reproduced with permission . Copyright 2018, Mary Ann Liebert Inc. G) A tripedal soft robot actuated based on the air propulsion actuator, H) air propelled limb and I) thrusts (arrows show the direction of air flow), and J) the horizontal displacement of the limb during bending.…”
Section: Soft Crawling Robots Enabled By Pressure Actuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2017, Mary Ann Liebert Inc. D) An omnidirectional soft robot consisting of nine (left) and three (right) modules, E) deformation of the soft cylinder under various conditions, and F) mechanism of crawling gait including contracted (red), pressurized (blue), and structure parts (green). Reproduced with permission . Copyright 2018, Mary Ann Liebert Inc. G) A tripedal soft robot actuated based on the air propulsion actuator, H) air propelled limb and I) thrusts (arrows show the direction of air flow), and J) the horizontal displacement of the limb during bending.…”
Section: Soft Crawling Robots Enabled By Pressure Actuationmentioning
confidence: 99%
“…Reconfigurable and omnidirectional soft robots have been developed for applications in unstructured environments . For instance, Zou et al developed a pneumatic‐driven, modular, and reconfigurable soft crawling robot, capable of both translation and rotation motions (Figure D) . Each module of the robot contains two different parts: the cube serving as the structural component and the soft pneumatic cylinder‐shaped actuator fixed to the sides (named S‐SC) or bottom of the cubes (named B‐SC).…”
Section: Soft Crawling Robots Enabled By Pressure Actuationmentioning
confidence: 99%
“…The V‐SPTA is seamless and effectively eliminates the need of rigid frames, resulting in a fully compliant vacuum‐powered actuator which is capable of continuous deformation. We demonstrate the performance and feasibility of V‐SPTAs with proof‐of‐concept designs on a rotatable crawling robot that can perform the highest turning speed of 25.7° s −1 , which is the fastest turning speed among all soft crawling robots . We also prototyped a V‐SPTAs‐driven car, a pipe‐climbing robot, a flexible arm, and a flexible wrist to demonstrate continuous rotation, diverse functions, and multiple DoFs capability.…”
Section: Combinations Of V‐sptas To Achieve Various Motionsmentioning
confidence: 98%
“…This innovative design effectively provides an additional significant DoF to V‐SPAs and enhances the capability of V‐SPAs. We have built upon our experience in V‐SPAs for the design of a reconfigurable omnidirectional robot and demonstrated that the newly designed vacuum‐powered soft pneumatic twisting actuator (V‐SPTA) can effectively twist 2° mm −1 of its own length. The maximum weight that a V‐SPTA with an initial height of 20 mm can actuate and rotate is more than 9 kg, which is over 473 times of its own weight.…”
Section: Combinations Of V‐sptas To Achieve Various Motionsmentioning
confidence: 99%
See 1 more Smart Citation